Membangun Generasi Sehat dan Aktif Melalui Olahraga di Sekolah Dasar - Syaharani, Adinda Regita; Nurhalizah, Afni; Hanan, Annida Lihasanati; Nababan, Indah Intansari; Masitoh, Siti; Mulyana, Agus (Indo-MathEdu Intellectuals Journal, 2024)
This article discusses the importance of building exercise habits from elementary school age to create a healthy and active lifestyle. The research method used in this study is a literature study research method. The sources of literature that are referenced in this study are books, scientific journals, articles, and various other references that are relevant to the research topic. Data Analysis of Literature Review Using Content Analysis. Research shows that sports participation can have a significant positive impact on children's cognitive, social, and emotional development. Additionally, this article highlights the additional benefits of exercise, such as improving motor skills, promoting teamwork, and reducing stress levels. This article suggests that by providing opportunities to participate in sports, elementary school can help build a foundation for a healthy and active lifestyle that will continue throughout life. Therefore, attention to academic education and the fulfillment of balanced nutrition is also important so that children can actively carry out daily activities. Let's build a healthier and more active future generation through sports in primary schools.